2013
DOI: 10.1118/1.4789579
|View full text |Cite
|
Sign up to set email alerts
|

Objective models of compressed breast shapes undergoing mammography

Abstract: Purpose: To develop models of compressed breasts undergoing mammography based on objective analysis, that are capable of accurately representing breast shapes in acquired clinical images and generating new, clinically realistic shapes. Methods: An automated edge detection algorithm was used to catalogue the breast shapes of clinically acquired cranio-caudal (CC) and medio-lateral oblique (MLO) view mammograms from a large database of digital mammography images. Principal component analysis (PCA) was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…This study utilizes the objective PCA model of patient breasts during acquisition of a cranio-caudal view mammographic image described by Feng et al 17 As the image of the compressed breast shape undergoing mammography is identical to the central angle (0 • ) projection of the compressed breast shape undergoing DBT, the mammography model forms the basis for the DBT model. The 3D breast volume (3DV) is built using the 2D breast shape (2DS) generated by the PCA model and an estimated curvature of the compressed breast volume.…”
Section: A 3d Model Of Breast Volume Undergoing Digital Breast Tommentioning
confidence: 99%
See 4 more Smart Citations
“…This study utilizes the objective PCA model of patient breasts during acquisition of a cranio-caudal view mammographic image described by Feng et al 17 As the image of the compressed breast shape undergoing mammography is identical to the central angle (0 • ) projection of the compressed breast shape undergoing DBT, the mammography model forms the basis for the DBT model. The 3D breast volume (3DV) is built using the 2D breast shape (2DS) generated by the PCA model and an estimated curvature of the compressed breast volume.…”
Section: A 3d Model Of Breast Volume Undergoing Digital Breast Tommentioning
confidence: 99%
“…To create this library, the parameters of the 4-component PCA model were selected according to the values in Table I. It has previously been shown that a 6-component PCA model results in greater accuracy of the modeled breast shape, 17 but the two additional latter components, which contribute the smallest amount of information to the shape, were deemed unnecessary for a low frequency signal such as x-ray scatter. This was confirmed by examination of the x-ray scatter maps resulting from five-and sixcomponent models.…”
Section: A 3d Model Of Breast Volume Undergoing Digital Breast Tommentioning
confidence: 99%
See 3 more Smart Citations